The ICA Joins Partner Organizations in Calling for the Protection of Archives and Cultural Heritage Amid Conflict in Iran, the Gulf Region, and the Eastern Mediterranean - Almeras, Clemence (ICA, 2026)
ICA expresses its deep concern over the escalation of hostilities affecting Iran, the Gulf Region, and the Eastern Mediterranean.